Homeward bound: annual breeding home range size and overlap in Broad-winged Hawks ( Buteo platypterus ) and the effects of sex, productivity, and ecoregion - Gallego García, Diego (2022)
Documenting home range size, and identifying the variables influencing it, is key to understanding raptor populationecology and to addressing conservation issues. The Broad-winged Hawk (Buteo platypterus, hereafter broadwing) is a small forest buteothat travels over 8,000 km between its breeding range in North America and wintering range in Central and South America. Althoughconspicuous during migration, its secretive behavior while nesting hinders data collection on behavior and movements during thebreeding season. We calculated breeding home ranges of 14 telemetry-tracked broadwings in northeastern USA and analyzed the effectsof intrinsic (sex and nest productivity) and extrinsic (ecoregion) variables, using autocorrelated kernel density estimations. Breedinghome ranges were 20 times larger in males than in females, in line with the strong division of labor between sexes observed in raptors.Breeding home ranges were larger in the most southerly ecoregion, suggesting that adults may need to move more to find prey for theirnestlings or the habitat is less suitable in this ecoregion. We found no effect of nest productivity, although sample size was small. Weassessed nest site fidelity and home range overlap across years for five adults. We found annual breeding home ranges overlapped (>0.85in all cases) and inter-annual nest distances were less than 200 m on average, indicating a strong fidelity to the breeding home rangeand to the nest site area. To our knowledge, this is the first study using telemetry data to calculate breeding home ranges of this secretiveforest raptor. Our findings indicate that broadwing breeding home ranges and nesting locations may remain stable over several years.Understanding and protecting the habitats used by nesting broadwings throughout their breeding range could be important to theirlong-term conservation.